Cannibalism and chaos in the classroom. Issue 1 (2nd January 2017) - Abernethy, Gavin M; McCartney, Mark
ABSTRACT: Two simple discrete-time models of mutation-induced cannibalism are introduced and investigated, one linear and one nonlinear. Both form the basis for possible classroom activities and independent investigative study. A range of classroom exercises are provided, along with suggestions for further investigations.